Genetic DNA profile in urine and hair follicles from patients who have undergone allogeneic hematopoietic stem cell transplantation. Issue 5 (September 2017) - Santurtún, Ana; Riancho, José A.; Santurtún, Maite; Richard, Carlos; Colorado, M. Mercedes; García Unzueta, Mayte; Zarrabeitia, María T.
Abstract: Biological samples from patients who have undergone allogeneic hematopoietic stem cell transplantation (HSCT) constitute a challenge for individual identification. In this study we analyzed the genetic profiles (by the amplification of 15 autosomic STRs) of HSCT patients found in different types of samples (blood, hair and urine) that may be the source of DNA in civil or criminal forensic cases. Our results show that while in hair follicles the donor component was not detected in any patient, thus being a reliable source of biological material for forensic identification, mixed chimerism was detected in urine samples from all patient, and no correlation was found between the time elapsed from the transplant and the percentage of chimerism. These results certainly have practical implications if the urine is being considered as a source of DNA for identification purposes in HSTC patients. Moreover, taking into consideration that chimerism was found not only in patients with leukocyturia (given the hematopoietic origin of leukocytes, this was expected), but also in those without observable leukocytes in the sediment, we conclude that an alternative source or sources of donor DNA must be implicated. Highlights: Allogenic HSCT constitutes a challenge for individual identification. Hair follicles are a reliable source for forensic identification in allogenic HSCT. Mixed chimerism was detected in urine from HSCT patients. Mixed chimerism was detected in patients without observable leukocytes in urine.